Orexin secretion abnormality involved in excessive somnolence in CNS lymphoma without hypothalamic lesions. (June 2019) - Hamada, Yasuhiro; Takata, Tadayuki; Kawakita, Rie; Kobara, Hideki; Okada, Masaki; Tamiya, Takashi; Kanbayashi, Takashi; Touge, Tetsuo; Deguchi, Kazushi; Masaki, Tsutomu
Highlights: Hypothalamic lesions cause excessive somnolence due to decreased orexin secretion. Excessive somnolence may occur even in cases without a hypothalamic lesion. Decreased CSF orexin levels suggest the involvement of hypothalamic impairment. CSF orexin is a useful marker for assessing potential hypothalamic somnolence. Abstract: A 72-year-old woman developed excessive somnolence as one of the symptoms of diffuse large B-cell lymphoma in the central nervous system (CNS). Although somnolence might be caused by reduced orexin secretion associated with hypothalamic lesions, neither brain MRI nor 18F-fluorodeoxyglucose positron emission tomography identified hypothalamic lesions. However, the decreased cerebrospinal fluid (CSF) orexin levels recovered to near normal values with improvement of somnolence after chemotherapy. The alteration of CSF orexin levels suggested the involvement of potential hypothalamic lesions. Therefore, measurements of CSF orexin levels may be useful for understanding the pathological background of somnolence in CNS lymphoma without hypothalamic lesions.